Evaluating pentraxin 3 as a diagnostic biomarker for diabetic retinopathy: a systematic review and meta-analysis - Reza Mohammadpour Fard; Negar Sadat Sherafat; Mohammad Rashno; Seyed Sobhan Bahreiny (Diabetology & Metabolic Syndrome)
Abstract Background Pentraxin 3 (PTX3), a novel biomarker of vascular inflammation and endothelial dysfunction, has been identified as a potential predictor of diabetic retinopathy (DR). This meta-analysis aimed to assess the association between circulating PTX3 levels and both the presence and severity of DR in patients with diabetes. Methods A systematic literature search was conducted across PubMed, Web of Science, Embase, Scopus, and Google Scholar up to January 2025. Observational studies comparing PTX3 levels between patients with and without DR, as well as proliferative (PDR) and non-proliferative (NPDR) stages, were considered. Standardized mean differences (SMD) with 95% confidence intervals (CI) were calculated using random effects models. Results A total of 15 studies comprising 1,339 patients with diabetes were included in this meta-analysis. The pooled analysis demonstrated significantly higher PTX3 levels in the DR group than in the non-DR controls (SMD = 1.232; 95% CI: 0.747, 1.718; p < 0.001). Subgroup analyses also indicated significantly elevated PTX3 levels in both NPDR (SMD = 0.928; 95% CI: 0.35, 1.50; p = 0.002) and PDR groups (SMD = 1.99; 95% CI: 0.83, 3.15; p = 0.001) compared to non-DR patients. Comparison of PTX3 levels between PDR and NPDR stages, suggested a possible increase in PDR patients (SMD = 0.635; 95% CI: -0.03, 1.30; p = 0.064). Meta-regression analysis identified HbA1c, BMI, and region as significant moderators of PTX3 levels. Conclusions The significant elevation of PTX3 in both NPDR and PDR underscores its potential as a biomarker for DR diagnosis and monitoring in clinical settings.